2009
DOI: 10.1016/j.bbagen.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic lethality of fortilin-null mutant mice by BMP-pathway overactivation

Abstract: Background Fortilin negatively regulates apoptosis and is overexpressed in cancer. However, the role of fortilin in mammalian development is not clear. Methods & Results In order to evaluate the physiological role of fortilin in vivo, we performed a targeted disruption of the fortilin gene in mice. Fortilin+/− mice have the ability to survive and exhibit normal growth, while fortilin−/− mice are embryonically lethal around the 3.5 days post-coitum (dpc). Cultured blastocysts from fortilin+/− embryos undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…Since then, the anti-apoptotic activity of TCTP has been reported on numerous occasions and in a range of different settings, which will be discussed below. Major support for the cytoprotective role of TCTP came from gene-knockout studies in mice, which demonstrated that TCTP-knockout was embryonic lethal, due to excessive apoptosis at an early embryonic state (Susini et al 2008;Chen et al 2007a;Koide et al 2009). The following mechanisms have been proposed to underlie the anti-apoptotic activity of TCTP/fortilin: …”
Section: Anti-apoptotic Activity: Discovery and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the anti-apoptotic activity of TCTP has been reported on numerous occasions and in a range of different settings, which will be discussed below. Major support for the cytoprotective role of TCTP came from gene-knockout studies in mice, which demonstrated that TCTP-knockout was embryonic lethal, due to excessive apoptosis at an early embryonic state (Susini et al 2008;Chen et al 2007a;Koide et al 2009). The following mechanisms have been proposed to underlie the anti-apoptotic activity of TCTP/fortilin: …”
Section: Anti-apoptotic Activity: Discovery and Mechanismsmentioning
confidence: 99%
“…The most impressive evidence for the importance of TCTP in early development was provided by TPT1-gene-knockouts in mice, which resulted in embryonic lethality (Susini et al 2008;Chen et al 2007a;Koide et al 2009). The explanation typically given for this effect was 'excessive apoptosis at an early embryonic state' (Susini et al 2008;Chen et al 2007a), whereas another report reasons that the lack of TCTP results in an overactivity of the BMP4 (bone morphogenetic protein 4) pathway, which is normally inhibited by TCTP (Koide et al 2009). The authors of this paper also show that in Xenopus embryos TCTP/fortilin is particularly important for the formation of neural tissue, even in the brain.…”
Section: Roles For Tctp In Early Developmentmentioning
confidence: 99%
“…This is underscored by the finding that gene knockout of TCTP in mice is embryonically lethal, due to excessive apoptosis early in embryogenesis [5][6][7]. TCTP has been found to bind to microtubules [8] and actin filaments [9], and to a range of other proteins [10].…”
Section: Introductionmentioning
confidence: 99%
“…Complete gene knockout of TCTP in Drosophila [28] and in mice [29][30][31] is embryonic lethal, and this effect was related to excessive apoptosis during early embryonic development of these mice. Koide et al [31] provided data showing that TCTP functions as an inhibitor of the BMP pathway in the early phases of development.…”
Section: • Tctp As a General Mitotic Regulatormentioning
confidence: 99%
“…The role of TCTP as an anti-apoptotic protein was highlighted in TCTP gene-knockout studies on mice [29][30][31], which demonstrated embryonic lethality due to excessive apoptosis at an early embryonic state. In 2009 two papers showed the importance of TCTP in preventing apoptotic cell death for the maintenance and development of T-cells.…”
Section: + -Atpasementioning
confidence: 99%